Análisis ingenieril y propuesta del mejoramiento continuo en un proceso de devoluciones de productos en una imprenta - Hidalgo, Gabriela (2009)
This study discusses the analysis and implementation of continuous improvement to reduce product returns in a print shop. To reduce the returns of product we made a study in the company to identify the problems that make these refunds occur frequently, causing big losses for waste. To find the major problems we used the technical MAFE (Modal Analysis of Failures and Effects). Once problems are found, selected the most critical problems and then find the reasons causing these problems with the help of the Ishikawa diagram. After identifying the causes that cause the two most significant problems within the company, proceeded to present the plan for improvement is mainly in the design of an internal plan of operation for the company, which will serve as a guide for implementation of the proposed improvement, then this is the specific action plans aimed primarily at the Kaizen Methodology, which is based on four fundamental aspects such as Empowerment, Cross Training, Teamwork and Leadership. This succeeded in reducing most of the problems, but also proposed other improvement plans to help fill the gaps found. Subsequently made the Cost - Benefit determined in which the internal rate of return, which gave a positive value, it makes the project feasible in purely positive terms for the company. Finally it was the calculation of the VAN, which was greater than zero it means that the proposed plan of improvement actually generates profits in the long term. The design of this improvement plan is to reduce the number of returns of products that carry with them high levels of waste.